Pengaruh Penerapan Sistem Keuangan Desa dan Partisipasi Masyarakat Terhadap Akuntabilitas Keuangan Desa Dengan Transparansi Keuangan Sebagai Variabel Moderasi - Kadir, Puspita; Memen Suwandi; Suhartono (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to examine the influence of the implementation of the village financial system and community participation on village financial accountability.The data used in the research is primary data collected through direct questionnaire surveys. Data analysis uses multiple regressionanalysis and moderated regression analysis with an absolute difference value approach. The results of research using multiple linear regression analysis show that the implementation of the village financial system has a positive and significant effect, and community participation has a positive and significant effect on village financial accountability. Analysis of moderating variables using the absolute difference value approach shows that the level of financial transparency is able to moderate the implementation of the village financial system towards village financial accountability, and the level of financial transparency is able to moderate community participation in village financial accountability.